2006
DOI: 10.1183/09031936.06.0035604
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of a school-based intervention to improve asthma management

Abstract: The present study investigated schools as an appropriate context for an intervention designed to produce clinical and psychological benefits for children with asthma.A total of 193 out of 219 (88.1%) children with asthma (aged 7-9 yrs) from 23 out of 24 (95.8%) schools completed the study. Intervention schools received a staff asthma-training session, advice on asthma policy, an emergency b 2 -agonist inhaler with spacer and whole-class asthma workshops. Nonintervention schools received no asthma-related input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…[47][48][49] The use of peers facilitated the reinforcement of health-related messages through consistent social contacts. 16,17 Using schools as the site of implementation also allowed the program to widely disseminate key asthma and smoking messages through a "cascade" of volunteer peers available at 1 site. 47…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49] The use of peers facilitated the reinforcement of health-related messages through consistent social contacts. 16,17 Using schools as the site of implementation also allowed the program to widely disseminate key asthma and smoking messages through a "cascade" of volunteer peers available at 1 site. 47…”
Section: Discussionmentioning
confidence: 99%
“…15 Although peer-led education can take place in many different contexts, school-based programs allow access to a large number of adolescents, and the continuous social contact helps to reinforce knowledge and behavior. [16][17][18] The Adolescent Asthma Action (Triple A) program is a peer-led intervention to improve the health and well-being of students with asthma in a supportive school environment. In a randomized controlled trial conducted in Australia, the investigators reported improved quality of life for adolescents with asthma, increased asthma knowledge, and decreased asthma-related school absenteeism.…”
mentioning
confidence: 99%
“…Encourage full participation in physical activities when students are well, offer reduced/modified activities if experiencing symptoms. There are many examples of successful education programmes for school children with asthma which incorporate some of the above-mentioned principles (28)(29)(30)(31).…”
Section: Challenges For the Schoolmentioning
confidence: 99%
“…Including standardised personalised management plans (eg, nationally agreed Allergy Action Plans for Children38) with correspondence to patients/parents explaining that it is their responsibility to share this with nurseries/schools may help. School-based interventions can improve health outcomes, such as asthma,39 and future integration of care between education authorities, schools and healthcare providers with key roles for school nurses is critically important.…”
Section: Discussionmentioning
confidence: 99%